PROCEDURES FOR IMPLEMENTING INTERNAL AUDIT IN THE MANAGEMENT SYSTEM DEPARTMENT OF PT PUPUK ISKANDAR MUDA ACEH UTARA - Hamdiah; Likdanawati; Sutriani; Windawati Br Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This practical work report contains internal audit implementation procedures at the Management System Department of PT. Pupuk Iskandar Muda. Meanwhile, the procedure for carrying out internal audits conducted by PT Pupuk Iskandar Muda consists of several starting from 1) Coordinating with the VP of the relevant work unit, 2) Making official audit team memos, 3) Appointing the head of the internal auditor team, 4) Making audit plans and schedules , 5) Opening of the audit, 6) Execution of the audit, 7) Closing of the audit, 8) Repair of discrepancies, 9) Monitoring of repairs, 10) Closing of the LKS, 11) Input of management review. There are several obstacles in the procedure for carrying out internal audits such as, Lack of Response from Internal Audit Management, just a waste of time, internal auditors are responsible for their main work, audit implementation is not effective.